2004
DOI: 10.4161/cbt.3.12.1238
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed genes in pancreatic ductal adenocarcinomas identified through serial analysis of gene expression

Abstract: Serial analysis of gene expression (SAGE) is a powerful tool for the discovery of novel tumor markers. The publicly available online SAGE libraries of normal and neoplastic tissues (http://www.ncbi.nlm.nih.gov/SAGE/) have recently been expanded; in addition, a more complete annotation of the human genome and better biocomputational techniques have substantially improved the assignment of differentially expressed SAGE "tags" to human genes. These improvements have provided us with an opportunity to re-evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 36 publications
6
44
0
1
Order By: Relevance
“…Moreover, preclinical studies in B-cell lymphoma and multiple myeloma showed CD74 was a novel and promising therapeutic target because binding of anti-CD74 monoclonal antibodies became rapidly cointernalized (38 -40). Recently, serial analysis of gene expression showed CD74 overexpression in pancreatic cancer (16). In the present study, we confirmed that CD74 was positive in 52 cases (78%) and was overexpressed in cancer cells compared with the pancreatic duct in clinical cases.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, preclinical studies in B-cell lymphoma and multiple myeloma showed CD74 was a novel and promising therapeutic target because binding of anti-CD74 monoclonal antibodies became rapidly cointernalized (38 -40). Recently, serial analysis of gene expression showed CD74 overexpression in pancreatic cancer (16). In the present study, we confirmed that CD74 was positive in 52 cases (78%) and was overexpressed in cancer cells compared with the pancreatic duct in clinical cases.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, pancreatic cancerspecific expression profiles using cDNA microarrays (11 -13), Affymetrix gene chip (14,15), and serial analysis of gene expression (16) have been used by many investigators. However, the molecular mechanisms of hepatic metastasis and perineural invasion in pancreatic cancer are far from clear.…”
mentioning
confidence: 99%
“…We and others have recently undertaken such analyses of normal pancreas and pancreatic adenocarcinoma (Crnogorac-Jurcevic et al, 2003;Logsdon et al, 2003;Hustinx et al, 2004;Grutzmann et al, 2005) and our cDNA array data showed overexpression of spermassociated antigen 1 (SPAG1) in cancer cells (Missiaglia et al, 2004).…”
Section: Introductionmentioning
confidence: 76%
“…The mortality rate of pancreatic cancer is so high in part because it usually does not produce symptoms until being metastasized and because there are no sensitive and specific tools to screen for early disease (33). Mucin-like protein DMBT1 binds to a variety of host proteins including IgA, C1q, lactoferrin, mucin 5B, and trefoil factor 2, which are all involved in innate immunity (34).…”
Section: Discussionmentioning
confidence: 99%